Mortars with phase change materials - Part I: Physical and mechanical characterization - Cunha, Sandra Raquel Leite (2015)
In a society with a high growth rate and increased standards of comfort arises the need to minimize the currently high energy consumption by taking advantage of renewable energy sources. The mortars with incorporation of phase change materials (PCM) have the ability to regulate the temperature inside buildings, contributing to the thermal comfort and reduction of the use of heating and cooling equipment, using only the energy supplied by the sun. However, the incorporation of phase change materials in mortars modifies its characteristics. The main purpose of this study was the production and characterization in the fresh and hardened state of mortars with incorporation of different contents of PCM in mortars based in different binders. The binders studied were aerial lime, hydraulic lime, gypsum and cement. For each type of binder, different mortars were developed with different content of PCM. The proportion of PCM studied was 0%, 20%, 40% and 60% of the mass of the sand. It was possible to observe that the incorporation of PCM in mortars caused differences in properties such as workability, microstructure, compressive strength, flexural strength and adhesion.